Application of Homograft Valved Conduit in Cardiac Surgery - Huyan, Yige; Chang, Yuan; Song, Jiangping (Frontiers in Cardiovascular Medicine, 2021)
Valved conduits often correct the blood flow of congenital heart disease by connecting the right ventricle to the pulmonary artery (RV-PA). The homograft valved conduit was invented in the 1960s, but its wide application is limited due to the lack of effective sterilization and preservation methods. Modern cryopreservation prolongs the preservation time of homograft valved conduit, which makes it become the most important treatment at present, and is widely used in Ross and other operations. However, homograft valved conduit has limited biocompatibility and durability and lacks any additional growth capacity. Therefore, decellularized valved conduit has been proposed as an effective improved method, which can reduce immune response and calcification, and has potential growth ability. In addition, as a possible substitute, commercial xenograft valved conduit has certain advantages in clinical application, and tissue engineering artificial valved conduit needs to be further studied.